2006
DOI: 10.1021/bi060440o
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inactivation of Glutaredoxin by Sporidesmin and Other Epidithiopiperazinediones,

Abstract: Glutaredoxin (thioltransferase) is a thiol-disulfide oxidoreductase that displays efficient and specific catalysis of protein-SSG deglutathionylation and is thereby implicated in homeostatic regulation of the thiol-disulfide status of cellular proteins. Sporidesmin is an epidithiopiperazine-2,5-dione (ETP) fungal toxin that disrupts cellular functions likely via oxidative alteration of cysteine residues on key proteins. In the current study sporidesmin inactivated human glutaredoxin in a time-and concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…The thiolcontaining mycotoxin sporidesmin (epidithiopiperazine-2,5-dione, #1456-55-9) inactivates human glutaredoxin in a time-and concentration-dependent manner. Under comparable conditions other thiol-disulfide oxidoreductases such as glutathione reductase, thioredoxin, and thioredoxin reductase, are unaffected by sporidesmin [143]. The data are consistent with the formation of intermolecular disulfides containing one adducted toxin per glutaredoxin with elimination of two sulfur atoms from the detected product [143].…”
Section: Sulfur Selenium and Tellurium Compoundssupporting
confidence: 73%
See 1 more Smart Citation
“…The thiolcontaining mycotoxin sporidesmin (epidithiopiperazine-2,5-dione, #1456-55-9) inactivates human glutaredoxin in a time-and concentration-dependent manner. Under comparable conditions other thiol-disulfide oxidoreductases such as glutathione reductase, thioredoxin, and thioredoxin reductase, are unaffected by sporidesmin [143]. The data are consistent with the formation of intermolecular disulfides containing one adducted toxin per glutaredoxin with elimination of two sulfur atoms from the detected product [143].…”
Section: Sulfur Selenium and Tellurium Compoundssupporting
confidence: 73%
“…Under comparable conditions other thiol-disulfide oxidoreductases such as glutathione reductase, thioredoxin, and thioredoxin reductase, are unaffected by sporidesmin [143]. The data are consistent with the formation of intermolecular disulfides containing one adducted toxin per glutaredoxin with elimination of two sulfur atoms from the detected product [143]. Thiolcontaining compounds based on the quinol pharmacophore 4-(hydroxycyclohexa-2,5-dienone) exhibit potent and selective antitumor activity against colon, renal, and breast carcinoma cell lines in vitro [144].…”
Section: Sulfur Selenium and Tellurium Compoundsmentioning
confidence: 97%
“…Thus, the development of a methodology for the specific detection of gliotoxin, especially under aqueous conditions and without the requirement for prior organic extraction and solvent removal, is significant because it enables direct identification of gliotoxin without specimen pre-treatment which may otherwise lead to gliotoxin loss or modification. Moreover, as with alternative strategies for mycotoxin detection [34], the reductive alkylation approach developed for detection of gliotoxin will also be useful in the detection of related ETP toxins such as sporidesmin A, as we have demonstrated, and other disulphide-or thiol-containing molecules [35,36].…”
Section: Discussionmentioning
confidence: 97%
“…Gliotoxin and related ETPs directly inactivate multiple enzymes and proteins in animal cells, including nuclear factor-kB (NF-kB), NADPH oxidase, and glutaredoxin, by conjugation to thiol groups [64][65][66]. It has been conclusively demonstrated that gliotoxin is taken up by animal cells in a GSH-dependent manner whereby this normally protective molecular species facilitates the concentration of gliotoxin within animal cells [59].…”
Section: Gliotoxin Impact On Animal Cellsmentioning
confidence: 99%